2017
DOI: 10.1016/j.jvoice.2016.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Using Rate of Divergence as an Objective Measure to Differentiate between Voice Signal Types Based on the Amount of Disorder in the Signal

Abstract: Objective/Hypothesis The purpose of this paper is to introduce rate of divergence as an objective measure to differentiate between the four voice types based on the amount of disorder present in a signal. We hypothesized that rate of divergence would provide an objective measure that can quantify all four voice types. Study Design 150 acoustic voice recordings were randomly selected and analyzed using traditional perturbation, nonlinear, and rate of divergence analysis methods. ty Methods We developed a ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 21 publications
1
14
0
1
Order By: Relevance
“…When comparing all subjects in both groups, χ 2 analysis showed that the reference SCR and ROD values established using the adult population could correctly classify voices as ordered or disordered with higher accuracy in adults compared with pediatric subjects. The higher proportion of correctly typed adult voices confirms that the adult normative reference values for SCR and ROD established by Calawerts et al 8 and Lin et al 9 are sufficient for classifying adult voices but not pediatric voices. In general, both SCR and ROD classified pediatric voices as 1 voice type higher than the voice type confirmed by spectral analysis.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…When comparing all subjects in both groups, χ 2 analysis showed that the reference SCR and ROD values established using the adult population could correctly classify voices as ordered or disordered with higher accuracy in adults compared with pediatric subjects. The higher proportion of correctly typed adult voices confirms that the adult normative reference values for SCR and ROD established by Calawerts et al 8 and Lin et al 9 are sufficient for classifying adult voices but not pediatric voices. In general, both SCR and ROD classified pediatric voices as 1 voice type higher than the voice type confirmed by spectral analysis.…”
Section: Discussionsupporting
confidence: 70%
“…9 Briefly, an SCR of 0 indicates high voice aperiodicity, and a value of 1 indicates more periodicity. A detailed description of ROD derivation and calculation can be found in Calawerts et al 8 Briefly, an ROD value of 0 indicates high periodicity in a voice sample, whereas a value of 1 indicates severe aperiodicity.…”
Section: Acoustic Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…12,24,25 25 Specifically, high degrees of noise can obscure the self-similarity property of voice signals, leading to increased computational errors and invalid calculations. 23,[41][42][43] Consequently, these findings suggest that D 2 analysis should be cautiously applied to voice signal types 1, 2, and 3 but not 4.…”
Section: Discussionmentioning
confidence: 92%
“…They reported an estimation of 2 for normal (mean value 2 = 0.014) and esophageal phonation (mean value 2 = 0.023) subjects. In [27], Calawerts et al calculated the largest Lyapunov exponent for type 1, type 2, and type 3 voices using the Kay Elemetrics database. Their results suggest an increase of the value of the largest Lyapunov exponent along with the type of the voice.…”
Section: Discussionmentioning
confidence: 99%